Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Shoup, Douglas; O'Brien, Daniel M.; Dhuyvetter, Kevin C. (My University, 2014)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_2014_02
Keywords: MF363; Economics; Crops; MF